The control Governance of information technologies and its reflection on the credibility of the financial statements - Fatlawi, Dr. Layla Naji Majeed AL (The journal of contemporary issues in business and government, 2023)
The aim of the research is to identify the role of the control governance of information technology in achieving the credibility of the financial statements in Iraqi banks, and the research dealt with the existence of a statistically significant relationship for the principles of control governance for information technology and internal control in the level of credibility of disclosure in the financial statements. The existence of a statistically significant relationship in the level of credibility of disclosure of the financial statements is attributed to several variables, as the study adopted the descriptive analytical approach to suit the nature of the study. The researcher used the questionnaire method as a tool for collecting data and information. A stratified sample of 19 managers in Iraqi banks was selected. The researcher relied on the Statistical Packages for Social Sciences (SPSS) program to analyze and present the data , Using frequencies, percentages, and one-way analysis of variance test to test the hypotheses, and after testing the significance of the phrases, the following results were drawn: Information technology governance fulfilled some formal conditions without taking into account the banks of the research sample with many legal frameworks, so its role is still limited in achieving the goals that were formed from Its purpose is to strengthen supervisory governance, as well as the humility of the knowledge and skill side of managers about the level of their evaluation of the degree of application of the principle of (support and delivery) in banks. The study also recommended the need to adopt the modern frameworks represented by the COBIT framework, as they are considered appropriate to keep pace with the rapid changes and developments of banking activities under the traditional and automated systems .